Early development of dietary patterns: transitions in the contribution of food groups to total energy—Feeding Infants and Toddlers Study, 2008. Issue 1 (December 2017) - Reidy, Kathleen; Deming, Denise; Briefel, Ronette; Fox, Mary; Saavedra, Jose; Eldridge, Alison
Abstract Background Early dietary patterns are critical to growth and development and play an important role in development of food preferences and habits. The objective of this paper is to describe when different foods enter the diet and how food consumption changes over the period of complementary feeding. Methods We analyzed cross-sectional 24-h dietary recall data from the Feeding Infants and Toddlers Study (FITS) 2008, a nationally representative sample of young children. Data are presented for 7 age groups: 6–8.9 months (n = 249), 9–11.9 months (n = 256), 12–14.9 months (n = 243), 15–17.9 months (n = 251), 18–20.9 months (n = 219), 21–23.9 months (n = 212) and 24–47.9 months (n = 1461).Per capita energy was calculated from major food groups and specific types of food within each food group. Results The predominant source of energy in the infant diet was milk (breast milk and infant formula), contributing 98% of energy at 0–3 months, and 91% at 4–5 months. At 6–8 months, when complementary feeding had begun for most infants, 69% of daily energy was coming from milk, 11% from grains, 6% from fruits, 5% from vegetables and 4% from mixed dishes. The diet then quickly transitioned until at 21–23.9 months, 26% of energy came from milk, with other key sources of energy being grains (17%), mixed dishes (14%), meats (12%) and sweets (12%). The period from 4 to 14 months was the most dynamic period of change regarding the introduction of complementary foods for all food groups, with a slower rate of change between 15 and 24 months. After 24 months, the diet stabilized and included less energy from milk (20%) and vegetables (4%) and more energy from mixed dishes (18%), grains (16%), and sweets (17%), and began to resemble adult diets. Conclusions Feeding in the first 24 months shapes dietary patterns, and thus provides a critical window of opportunity to shape subsequent dietary patterns and eating habits. Findings from FITS identified high sweet and low vegetable consumption as key issues. Education is needed for health care professionals and parents on feeding during this important period. These findings can be used to support the development of specific and actionable feeding guidance for parents.